An effective cluster based data dissemination in a hybrid cellular ad hoc network. (27th December 2018) - Rajkumar, M.; Suresh, R.M.; Sasikumar, R.
Summary: Recent research works have shown much interest in incorporating ad hoc networks with a cellular network to improve the data dissemination. The primary challenge of disseminating data over a hybrid network is to select the mode of operation between the cellular and ad hoc interfaces effectively. This work proposes Adaptive Data Dissemination (ADD) algorithm that enables the nodes to switch between the cellular and ad hoc interfaces and reduces the burden of the base station without degrading the communication efficiency. The proposed algorithm partitions the entire network into small clusters and selects the cluster head for each cluster based on the link‐worth function. This algorithm divides the transmission range of a base station into two regions such as interior and exterior. The interior region is nearer to the base station, while the exterior constitutes the border region of the base station's coverage area. The cluster heads in the interior region choose the cellular mode and retrieve the data from the base station directly. The cluster head in the exterior region initially chooses the ad hoc mode and later on chooses the cellular mode in the unavailability of demanding data in the neighboring cluster. The ADD algorithm does not allow the same node to act as a cluster head for a long time as the energy will get drained‐off quickly. Therefore, the proposed approach dynamically exchanges the role of the cluster head with the cluster members based on the link‐worth function. The base station deals only with the cluster heads in the interior range, and hence, minimizing the resource consumption at the base station. Nodes exchange as many chunks as possible using ad hoc links to reduce cellular network usage. The success of the proposed approach is evaluated using NS2 simulation.